Expression of VEGF, its receptors, and HIF-1α in Dupuytren's disease. (August 2013) - Holzer, Lukas A; Cör, Andrej; Pfandlsteiner, Gerhard; Holzer, Gerold
<x xml:space="preserve">Abstract</x> Background and purpose — Dupuytren's disease (DD) is a benign fibroproliferative process that affects the palmar fascia. The pathology of DD shows similarities with wound healing and tumor growth; hypoxia and angiogenesis play important roles in both. We investigated the role of angiogenic proteins in DD. Patients and methods — The expression of vascular endothelial growth factor (VEGF), its receptors vascular endothelial growth factor receptor 1 (VEGFR1) and vascular endothelial growth factor receptor 2 (VEGFR2), hypoxia-inducible factor alfa (HIF-1α), and alfa-smooth muscle actin (α-SMA) were analyzed immunohistochemically in fragments of excised Dupuytren's tissue from 32 patients. We compared these values to values for expression in a control group. Results — 15 of 32 samples could be attributed to the involutional phase (α-SMA positive), whereas 17 samples were considered to be cords at the residual phase (α-SMA negative). In the involutional phase, the HIF-1α and VEGFR2 expression was statistically significantly higher than in the residual phase and in the controls. Interpretation — Both the VEGFR2 receptor and HIF-1α were expressed in α-SMA positive myofibroblast-rich nodules with characteristics of DD in the active involutional phase. Thus, hypoxia and (subsequently) angiogenesis may have a role in the pathophysiology of DD.